Spatial-temporal characteristics and drivers of urban built-up areas land low-carbon efficiency in China - Jin Guo; Pengfei Feng; Han Xue; Jinli Xue (Scientific Reports)
Abstract Understanding the evolution of low-carbon efficiency in urban built-up areas is essential for developing countries striving to meet sustainable development goals. However, the mechanisms driving low-carbon efficiency and the associated development pathways remain underexplored. This study applies the Global Data Envelopment Analysis (DEA) model, the Global Malmquist-Luenberger Index, and econometric models to evaluate low-carbon efficiency and its determinants across China’s urban built-up areas from 2010 to 2022. The findings reveal a significant increase in efficiency, from 0.555 in 2010 to 0.785 in 2022, reflecting an overall improvement of 41.4% (P < 0.05). Spatially, low-carbon efficiency demonstrates a pronounced “east-high and west-low” distribution, highlighting regional disparities and spatial correlations. Temporal changes in low-carbon efficiency are primarily driven by technological advancements and shifts in the technological frontier. However, the disproportionate efficiency gains during periods of high resource input suggest inefficiencies in production factor allocation, particularly in densely populated urban centers. Unlike natural endowments, concentrated factor inputs in such cities often impede efficiency improvements. The findings underscore the need for context-sensitive development strategies, as a one-size-fits-all model may not address the diverse challenges posed by regional disparities. By leveraging market mechanisms to optimize resource allocation and strengthen interregional spatial connectivity, this study provides actionable insights for promoting sustainable land development in developing economies.